Enhancement of Office Procedure in Human Resource Department at ABC Restaurant in Quezon City: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
ABC Restaurant is a food company that specializes in traditional Filipino cuisine and offers high-quality and delicious products. The company has provided nutritious and varied cuisine since 2007 and is committed to providing the tastiest and safest food products globally. Dining out has become a common part of people's lives, and the rise of food companies like ABC Restaurant is a key factor in economic growth. The company values its customers and provides excellent service and value. Six men and one woman who work at ABC Restaurant were interviewed by the researchers using a qualitative descriptive method. The purpose of the study was to learn more about the restaurant's operations and pinpoint areas that could use improvement. The interview's first section concentrated on the functions and demographics of the employees. The second part, however, included a questionnaire about suggested extra steps to improve the production process. After conducting numerous studies, the researchers came up with potential improvements and efficiency boosts for the production process. They suggested using virtual interviews, like phone interviews, to speed up the hiring process and make sure the human resources department is dependable and effective. These suggestions deal with potential future problems and enhance ABC Restaurant's overall effectiveness.
Keywords: Restaurant; Office Procedure; Termination; Resignation